Dicoumarol, an NQO1 inhibitor, blocks cccDNA transcription by promoting degradation of HBx - Cheng, Sheng-Tao; Hu, Jie-Li; Ren, Ji-Hua; Yu, Hai-Bo; Zhong, Shan; Wai Wong, Vincent Kam; Kwan Law, Betty Yuen; Chen, Wei-Xian; Xu, Hong-Mei; Zhang, Zhen-Zhen; Cai, Xue-Fei; Hu, Yuan; et al. (Journal of hepatology, 2021)
Current antiviral therapies help keep HBV under control, but they are not curative, as they are unable to eliminate the intracellular viral replication intermediate termed covalently closed circular DNA (cccDNA). Therefore, there remains an urgent need to develop strategies to cure CHB. Functional silencing of cccDNA is a crucial curative strategy that may be achieved by targeting the viral protein HBx. We screened 2,000 small-molecule compounds for their ability to inhibit HiBiT-tagged HBx (HiBiT-HBx) expression by using a HiBiT lytic detection system. The antiviral activity of a candidate compound and underlying mechanism of its effect on cccDNA transcription were evaluated in HBV-infected cells and a humanised liver mouse model. Dicoumarol, an inhibitor of NAD(P)H:quinone oxidoreductase 1 (NQO1), significantly reduced HBx expression. Moreover, dicoumarol showed potent antiviral activity against HBV RNAs, HBV DNA, HBsAg and HBc protein in HBV-infected cells and a humanised liver mouse model. Mechanistic studies demonstrated that endogenous NQO1 binds to and protects HBx protein from 20S proteasome-mediated degradation. NQO1 knockdown or dicoumarol treatment significantly reduced the recruitment of HBx to cccDNA and inhibited the transcriptional activity of cccDNA, which was associated with the establishment of a repressive chromatin state. The absence of HBx markedly blocked the antiviral effect induced by NQO1 knockdown or dicoumarol treatment in HBV-infected cells. Herein, we report on a novel small molecule that targets HBx to combat chronic HBV infection; we also reveal that NQO1 has a role in HBV replication through the regulation of HBx protein stability. Current antiviral therapies for hepatitis B are not curative because of their inability to eliminate covalently closed circular DNA (cccDNA), which persists in the nuclei of infected cells. HBV X (HBx) protein has an important role in regulating cccDNA transcription. Thus, targeting HBx to silence cccDNA transcription could be an important curative strategy. We identified that the small molecule dicoumarol could block cccDNA transcription by promoting HBx degradation; this is a promising therapeutic strategy for the treatment of chronic hepatitis B. [Display omitted] •Dicoumarol, a competitive NADPH quinone oxidoreductase (NQO1) inhibitor, is identified as an inhibitor of HBx expression.•NQO1 stabilises HBx protein by inhibiting 20S proteasome-mediated protein degradation.•NQO1 knockdown or dicoumarol treatment blocks cccDNA transcription by establishing a repressive chromatin structure.•Dicoumarol exhibits potent antiviral activity in HBV-infected hepatocytes and a humanised liver mouse model.